Bibliometric analysis on creative industry project costing methodologies - Quiceno-Opina, Johan S. (2021)
Objective. To analyze the research trends in relation to the costing of creative economy projects. Methods. A bibliometric analysis was developed from the Scopus database, applying a search equation and calculating bibliometric indicators such as quantity, quality and identification of emerging topics from documents published between 1970 and 2020. Results. The creative industries has been a topic of interest to researchers since 1997; however, it is possible to observe a continuous growth from the year 2001, date that coincides with the first publications made by Professor John Howkins, in the same way it is identified that from the social sciences show a greater interest in the subject. Conclusions. There is evidence of an impact and growth in the area of study, which validates the convenience of research projects oriented to costing methodologies for creative industry projects.